Organic magnetic nanoparticles catalyze CO2 capture in hydrogen-bonded nanocages via water-driven crystallization - Tian Wang; Aliakbar Hassanpouryouzband; Mengge Fan; Chalachew Mebrahtu; Lunxiang Zhang; Yongchen Song (Nature Communications)
Abstract Limiting global warming increasingly relies on the development of environmentally friendly CO2 capture strategies. Crystallization is renowned for versatile separation and purification, yet traditional compound crystallization-based CO2 capture still necessitates intricate preparation processes, stringent reaction conditions, and high regenerative energy consumption. As an ambitious sustainability goal, natural water could be used as a precursor of crystallization to construct hydrogen-bonded water cages for CO2 capture, but main obstacles are slow crystallization kinetics and low capture capacity. Here, a water-activation-induced crystallization strategy by organic magnetic nanoparticles (Methionine@Fe3O4) has been proposed for efficient CO2 capture. Local water ordering strengthened by hydrophobic amino acids and abundant nucleation sites provided by nanoparticles create hotspots for hydration phase transition and crystal growth, with a CO2 capture capacity of 118.7 v/v (22.7 wt%). Favorable biocompatibility and stable performance are conducive to the industrial application of this nanomaterial, and the excellent magnetic recyclable property enables simple separation from clean water. This strategy demonstrates an extraordinary CO2 capture potential compared to state-of-the-art systems, thus providing an inspiration for sustainable CO2 capture and storage with zero resource depletion (ZRD).